Success through a positive mental attitude - "Hill, Napoleon" (New York, 1977)
The great Danish philosopher and religious thinker, Soren Kierkegaard, once wrote, "It is the sign of a good book when the book reads you." You told in your hands such a book- one that has not only become a classic in the self-help field, but also has that rare ability to relate to your problems, sympathize with them, and then advise you on their solutions as a wise old friend would.
Keywords: Power of the mind